Metaverse Dalam Perspektif Ilmu Hukum - Natsir, Muhammad (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
In this article, several legal views regarding metaverse law are analyzed and discussed. In addition, this article analyzes the new changes that the metaverse brings to our lives, a brief history and new concepts of the metaverse, the application of artificial intelligence in the metaverse, the six main challenges and legal problems of the metaverse, and such scientific problems. As a result of this article, the author provides several suggestions and recommendations for the development of Uzbekistan's digital legislation at the end.